Cell death and thymic tolerance. Issue 1 (30th April 2017) - Daley, Stephen R.; Teh, Charis; Hu, Daniel Y.; Strasser, Andreas; Gray, Daniel H.D.
Summary: The differentiation of hematopoietic precursors into the many functionally distinct T‐cell types produced by the thymus is a complex process. It proceeds through a series of stages orchestrated by a variety of thymic microenvironments that shape the T‐cell developmental processes. Numerous cytokine and cell surface receptors direct thymocyte differentiation but the primary determinant of cell fate is the engagement of the T‐cell antigen receptor (TCR). The strength of the TCR signal and the maturation stage of the thymocyte receiving it can direct the various differentiation programs or, alternatively, end the process by inducing cell death. The regulation of thymocyte death is critical for the efficiency of thymic T‐cell differentiation and the preservation of immune tolerance. A detailed knowledge of mechanisms that eliminate thymocytes from the T‐cell repertoire is essential to understand the "logic" of T‐cell selection in the thymus. This review focuses on the central role of the BCL‐2 family of proteins in the apoptotic checkpoints that punctuate thymocyte differentiation and the consequences of defects in these processes.